Landing centers and availability of fish species in fish markets of Mymensingh town (Journal of the Bangladesh Agricultural University, 2012)
An investigation was carried out on fish landing centers, fish markets and fish fauna of the Mymensingh town to   overview the location of the fish landing/entering centers, the source of supply and availability of fisheries organisms   in Mymensingh town. The investigation was conducted from October 2009 to September 2010 in sixteen landing   centers and markets of Mymensingh town. Among a total of 122 species of fishes were available of which, 113 were   finfish and 9 were shellfish. Out of 113 finfish, 85 were freshwater fish species, 14 were exotic species, 14 were   marine species, 7 were prawn /shrimps and 2 were mud crab and tortoise. Different types of freshwater fish, marine   fish, crustacean and dry fish were found in Mymensingh town. The most abundant freshwater fish species were Catla   catla, Labeo rohita, Clarias batrachus, Cirrhinus cirrhosus, Channa punctatus. Among the marine fishes Lates   calcarifer, Euthynnus affinis and Mugil cephalus were recorded. The shellfishes, Macrobrachium rosenbergii and   Penaeus monodon were most abundant. Significant amount of carps were imported from inside and outside of the   districts. Besides the carps, small quantities of other fish, e.g, hilsha, catfish, tilapia, small indigenous fish, prawn and   shrimp and other fish including marine can be seen in the fish landing centers and fish markets in Mymensingh town.   Trains, buses, trucks and pickups were used as transport of fish to the landing centers from outside of Mymensingh   town. Virtually most of the fish (84.6 %) were brought from different areas of the district and adjacent district like   Netrokona, Jamalpur, Gazipur and Kishoreganj. The rest (15.4 %) were brought from external source in Mechhua   bazar, Natun bazar, Sankipara bazar, Charpara bazar and Kathgola bazar. Main source of the fishes were different   ponds, haors, beels and rivers of Mymensingh and adjacent districts.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.11046   ]J. Bangladesh Agril. Univ. 9(2): 311318, 2011